Influence of modification of supported palladium systems by polymers: PVP, AMPS and AcrAMPS on their catalytic properties in the reaction of transformation of biomass into fuel bio-components. (1st July 2020) - Szubiakiewicz, Elzbieta; Modelska, Magdalena; Brzezinska, Magdalena; Binczarski, Michal J.; Severino, Courtney J.; Stanishevsky, Andrei; Witonska, Izabela
Graphical abstract: Highlights: Hydrogenation of furfural is reported on modified by PVP Pd/SiO2 catalysts. 5%Pd/AMPS-SiO2 catalyst allows direct conversion of furfural into THFA. The modification of SiO2 by PVP limited the adsorption of furfural by carbonyl group. The Pd catalysts are active in the reduction of furfurals obtained from biomass. Abstract: Catalytic systems based on highly dispersed Pd nanoparticles deposited on SiO2 modified with PVP, AMPS and AcrAMPS were prepared and used in the hydrogenation of furfural obtained by the aqueous phase acidic hydrolysis of waste biomass (sugar beet pulp, sugar beet leaves, and brewing grain) from the food industry. Pd/PVP/SiO2 catalysts containing 50 g of Pd per 1 kg of catalyst were characterized by high activity in studied process, but lower selectivity to THFA in comparison to Pd/AMPS-SiO2 or Pd/AcrAMPS-SiO2 catalysts. The modification of SiO2 by PVP followed by the palladium catalyst loading, limited the adsorption of furfural by carbonyl group which probably leads to the improvement in THFA formation, which was confirmed by FTIR studies. The physico-chemical properties of the obtained palladium catalysts were investigated by XRD, CO chemisorption, TPR H2, TG-DTA-MS and BET techniques. The ICP-AES indicated no leaching of metal into the environment during furfural reduction, which confirms the stability of the Pd/PVP/SiO2, Pd/AMPS-SiO2 and Pd/AcrAMPS-SiO2 systems in the studied process.